A Random Laser Production Using Fluorescein Dye Doped TiO2 Nanoparticles - Al-Arab, Husam S.; Al-Kadhemy, Mahasin F. H.; Saeed, Asrar Abdulmunem (Iraqi Journal of Science, 2019)
A random laser has been produced using Fluorescein dye solution in water, with concentration of (8 10-5 M); doped with (0.001g) TiO2 Nanoparticles with the particle size of (15.7 nm). A blue diode laser of 450 nm wavelength has been used as an optical pumping source. The wavelength of the random laser was 523 nm and the intensity was 5.44 mW